Mastalgia Assesment and Hormonal Correlations in Patients with Polycystic Ovary Syndrome - Emel Kıyak Çağlayan; Levent Seçkin; Ayşe Yeşim Göçmen; Aylin Okur; Ergin Arslan; Halil İbrahim Serin; Kasım Çağlayan; Yaprak Engin Üstün (Medical Network, 2016)
OBJECTIVE: The aim of this study is the assesment of relationship between mastalgia and hormonal parameters and frequency of mastalgia in polycystic ovary syndrome (PCOS). STUDY DESIGN: 141 patients who are admitted to our clinic were included in this study after taking their informed consent. 78 patients who were diagnosed as PCOS according to the Rotterdam Criteria constitute the patient group. 63 patients who are admitted for routine control and had no hormonal pathology constitute the control group. Age of the patients were noted, complaints of mastalgia were questioned and hormonal parameters (Follicle-Stimulating Hormone (FSH), Luteinizing Hormone (LH), Estradiol (E2), Testosterone, Dehydroepiandrosterone Sulphate (DHEAS), Thyroid-Stimulating Hormone (TSH), Body Mass Index (BMI)) were recorded. RESULTS: Frequency of mastalgia was found as 24.4% in PCOS group and 33.3% in control group and there is no statistical difference (p>0.05). It is apparent that the PCOS group, when compared with the control group, is characterized by higher LH levels and higher Testosterone, DHEAS and TSH levels (p<0.001, p<0.001, p=0.019, p=0.04) CONCLUSION: Although there were different LH and Testosterone levels, we couldn't find statistical difference for the frequency of mastalgia between PCOS and the control group. There were no relationship between age, BMI and hormonal parameters in patients with mastalgia, so PCOS couldn't be a factor that effects the frequency of mastalgia. It seems that in mastalgia positive PCOS group, age and BMI effects the frequency of mastalgia but we can't say the same for hormones.